2021
DOI: 10.7150/ijbs.51207
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel immune-related lncRNA signature as a prognostic classifier for endometrial carcinoma

Abstract: Endometrial carcinoma (EnCa) is one of the deadliest gynecological malignancies. The purpose of the current study was to develop an immune-related lncRNA prognostic signature for EnCa. In the current research, a series of systematic bioinformatics analyses were conducted to develop a novel immune-related lncRNA prognostic signature to predict disease-free survival (DFS) and response to immunotherapy and chemotherapy in EnCa. Based on the newly developed signature, immune status and mutational loading between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…In severe aplastic anemia (SAA) patients, the decreased expression of AF117829.1 upregulates the activity of CD8 + T lymphocytes, which means lncRNA may be associated with the regulation of the immune microenvironment ( Li et al, 2021 ). POC1B-AS1 is also a risk factor in the prognostic model of endometrial carcinoma ( Liu J. et al, 2021 ). In psoriasis, CCDC18-AS1, regarded as immune-related lncRNA, can be a potential diagnostic biomarker ( Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In severe aplastic anemia (SAA) patients, the decreased expression of AF117829.1 upregulates the activity of CD8 + T lymphocytes, which means lncRNA may be associated with the regulation of the immune microenvironment ( Li et al, 2021 ). POC1B-AS1 is also a risk factor in the prognostic model of endometrial carcinoma ( Liu J. et al, 2021 ). In psoriasis, CCDC18-AS1, regarded as immune-related lncRNA, can be a potential diagnostic biomarker ( Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, for example, Dong et al developed a 7-lncRNA signature for predicting UCEC prognosis; 24 Liu et al identified 13 immune-related lncRNAs closely related to UCEC overall survival. 25 For now, no molecular subtyping system based on immunerelated lncRNAs has been reported.…”
Section: Impact Statementmentioning
confidence: 99%
“…[13]. [14], [15].In this study, we constructed for the rst time a lncRNA model including 8 immune-related lncRNAs, and veri ed the accuracy of this model as a marker for the survival status of soft tissue sarcoma. First, we analyzed the transcriptome data of TCGA SARC and obtained the lncRNA co-expressed with immune genes.…”
Section: Discussionmentioning
confidence: 96%